An Updated Design Formula for Predicting the Compressive Strength of Plate: Elastic Buckling and Ultimate Compressive Strength - Do Kyun Kim; Hee Yeong Yang; Shen Li; Seungjun Kim (Journal of Marine Science and Engineering)
In the present study, a simplified and useful design formula is proposed to predict the ultimate strength of a plate under longitudinal compression. The shape of the elastic buckling strength (<semantics>σxE</semantics>) equation is utilised and adjusted to predict the ultimate compressive strength of the plate. In total, 600 cases of reasonable plate scenarios are selected to update the design formula by broadly considering the plate geometry (i.e., plate length, breadth, and thickness), material property (i.e., elastic modulus and yield strength), and initial deflection. The proposed formula, including the factor or coefficient for correction (<semantics>Cf</semantics>) may help ocean and shore (including onshore, offshore and nearshore) structural engineers improve safety and design the unstiffened plate element used in shipbuilding and oil and gas.